Association Between Postoperative Body Temperature and All-Cause Mortality After Off-Pump Coronary Artery Bypass Graft Surgery: A Retrospective Observational Study. (May 2020) - Nam, Karam; Jo, Woo Young; Kwon, Seok Min; Kang, Pyoyoon; Cho, Youn Joung; Jeon, Yunseok; Kim, Tae Kyong
Abstract : BACKGROUND: Inadvertent perioperative hypothermia is common in patients undergoing off-pump coronary artery bypass grafting (OPCAB). We investigated the association between early postoperative body temperature and all-cause mortality in patients undergoing OPCAB. METHODS: We reviewed the electronic medical records of 1714 patients who underwent OPCAB (median duration of follow-up, 47 months). Patients were divided into 4 groups based on body temperature at the time of intensive care unit admission after surgery (moderate-to-severe hypothermia, <35.5°C; mild hypothermia, 35.5°C–36.5°C; normothermia, 36.5°C–37.5°C; and hyperthermia, ≥37.5°C). Cox proportional hazards models were used to assess the association between body temperature and all-cause mortality. The association between early postoperative changes in body temperature and all-cause mortality was also assessed by dividing the patients into 4 categories according to the body temperature measured at postoperative intensive care unit admission and the average body temperature during the first 3 postoperative days. RESULTS: Compared to the normothermia group, the adjusted hazard ratios of all-cause mortality were 2.030 (95% confidence interval, 1.407–2.930) in the moderate-to-severe hypothermia group and 1.445 (95% confidence interval, 1.113–1.874) in the mild hypothermia group. Patients who were hypothermic at postoperative intensive care unit admission but attained normothermia thereafter were at a lower risk of all-cause mortality compared to patients who did not regain normothermia (adjusted hazard ratio, 0.631; 95% confidence interval, 0.453–0.878), while they were still at a higher risk of all-cause mortality than those who were consistently normothermic (adjusted hazard ratio, 1.435; 95% confidence interval, 1.090–1.890). CONCLUSIONS: Even mild early postoperative hypothermia was associated with all-cause mortality after OPCAB. Patients who regained normothermia postoperatively were at lower risk of all-cause mortality compared to those who did not.